La incidencia de los tributos municipales recaudados por el gobierno autónomo descentralizado del cantón latacunga en el presupuesto municipal enero – diciembre del 2011 - Camino Jácome, Luis Eduardo (2015)
Within this research project is looking for a priority focus to the management of municipal taxes under the autonomous government decentralized Latacunga, where perceive money as amounts for management of taxes paid by citizens through taxes; for this theoretical bases are conceptualized and are chosen and instruments that determine the ease of study apply. The methodology used is the analytic and synthetic, also states that the interview and survey and research techniques were applied to taxpayers and officials GAD Canton Latacunga with valuable and necessary for the development of the study of the legwork information